Modelling photosynthetic efficiency (α) for the light-response curve of cocksfoot leaves grown under temperate field conditions - Peri, Pablo Luis (2005)
Net photosynthetic rate was measured from the youngest fully expanded leaves of field grown cocksfoot (Dactylis glomerata L.) in open pastures and under trees in the Lincoln University silvopastoral experiment (New Zealand). The photosynthetic efficiency (α) and convexity (θ) of the light-response curve were derived from 209 fitted non-rectangular hyperbola functions. There was no relationship between θ and any of the environmental or management variables with a stable mean value of 0.96. For α, individual functions were required for temperature (10–31 ◦C), nitrogen (N) concentration (1.5–5.9% N), water status (expressed as pre-dawn leaf water potential, ψlp) (−0.01 to −1.6 MPa), regrowth duration (20–60 days), and different times (up to 180 min) under moderate (850–950 mmol m−2 s−1 photon irradiance) and severe (85–95 mmol m−2 s−1 photon irradiance) shade. The highest α of 0.036 mmol CO2/mmol photon irradiance was found in non-limiting conditions and defined as the standardised maximum (αs = 1). Values of αs = 1 were measured in optimum ranges of 10–24 ◦C, 4.0–5.9% N, −0.01 to −1.0 MPa and 20 days regrowth. In addition, values of αs reached a steady-state asymptote of 0.74 after 60 min of severe shade and 0.92 after 40 min of moderate shade. Individual functions of α could not be integrated into a simple multiplicative model but a ‘law of the minimum factor’ model was appropriate. Predicted results from this model were then validated with 46 independent data points collected when at least two factors were outside their optimum range. The model accounted for 88% of the variation in observed α values. This research has derived functional relationships for α that can be used to assist predictions of leaf photosynthesis and ultimately pasture growth by their inclusion in canopy photosynthesis models.